Powered Air Purifying Respirator (PAPR) restores the N95 face mask induced cerebral hemodynamic alterations among Healthcare Workers during COVID-19 Outbreak - Bharatendu, Chandra (ELSEVIER, 2021)
10.1016/j.jns.2020.117078